Cardiac troponins--Translational biomarkers in cardiology: Theory and practice of cardiac troponin high-sensitivity assays - Adamcova, Michaela; Popelova-Lencova, Olga; Jirkovsky, Eduard; Simko, Fedor; Gersl, Vladimir; Sterba, Martin (BioFctors, 2016)
Tn is a unique translational biomarker in cardiology whose potential has not been diminished in the new era of high sensitive assays. cTns can be valuable markers in cardiac diseases as well as in infectious diseases and respiratory diseases. Furthermore, the role of cTns is growing in the routine evaluation of cardioxicity and in determining the efficacy/safety ratio of novel cardioprotective strategies in clinical settings. cTns can detect myocardial injury not only in a wide spectrum of laboratory animals in experimental studies in vivo, but also in isolated heart models or cardiomyocytes in vitro. The crucial issue regarding the cross-species usage of cardiac troponin investigation remains the choice of cardiac troponin testing. This review summarizes the recent proteomic data on aminoacid sequences of cTnT and cTnI in various species, as well as selected analytical characteristics of human cardiac troponin high-sensitivity assays. Due to the highly phylogenetically conserved structure of troponins, the same bioindicator can be investigated using the same method in both clinical and experimental cardiology, thus contributing to a better understanding of the pathogenesis of cardiac diseases as well as to increased effectiveness of troponin use in clinical practice. Measuring cardiac troponins using commercially available human high-sensitivity cardiac troponin tests with convenient antibodies selected on the basis of adequate proteomic knowledge can solve many issues which would otherwise be difficult to address in clinical settings for various ethical and practical reasons. Our survey could help elaborate the practical guidelines for optimizing the choice of cTns assay in cardiology.
Keywords: Heart Diseases; troponin T; Biological Assay; Biomarkers; proteomika; Troponin I; biologické markery; troponin I; nemoci srdce; Myocardium; Troponin T; Proteomics; Humans; lidé; biotest; myokard